Politik Kantor PNS: Sudut Pandang Aceh - Nurhadisah, Nurhadisah; Hidayat, Muhammad Rahmat (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
This study examines office politics in the context of Aceh's civil servant (PNS) perspective using SEM PLS method. Involving 107 respondents, the research analyzes the relationship between internal office relationships, communication, and decision-making. The main findings highlight the positive correlation between internal relationships and communication, playing a crucial role in shaping office politics dynamics. Open communication facilitates collaboration, reduces conflicts, and influences better decision-making. Inclusive leadership is identified as a factor strengthening relationships and collaboration. The study underscores the importance of transparency in communicating policies and decision-making processes to prevent misunderstandings. These results offer insights into key factors for understanding PNS office politics and its impact on organizational effectiveness in Aceh.